The Influence of PAI Teachers' Pedagogical Competence on The Emotional Intelligence - Sabila, Aulia Himma; Nisa, Khoirun; Pratiwi, Irene Thaurisa Erma; Mukminati, Siti Dini; Wijaya, Vivi Febiola; Fidiyaningsih, Isna (Assyfa Journal of Islamic Studies, 2024)
This research aims to analyze the influence of Islamic Religious Education (PAI) teachers' pedagogical competence on the emotional intelligence of Class VIII students at SMPIT Baitul Qur’an Al Jahra Magetan. PAI teachers' pedagogical competence includes understanding student characteristics, learning planning, teaching method utilization, and learning outcome evaluation, while emotional intelligence is measured based on aspects of self-awareness, emotional management, motivation, empathy, and social skills (Goleman, 2009). This study uses a quantitative approach with a correlational method. The research population consists of all female Class VIII students (104 students), with a sample of 51 respondents selected using the Slovin formula. Data were collected through Likert scale-based questionnaires and analyzed using validity, reliability, normality, linear regression tests, and hypothesis tests (t-test and F-test) using SPSS version 25. This research analyzes the significant influence of teacher pedagogical competence on students' emotional intelligence. Pedagogical competence, which includes the teacher's ability to understand student characteristics, design effective learning, and create a supportive learning environment, is found to play a crucial role in shaping students' emotional intelligence. This influence occurs through a learning process that not only focuses on cognitive aspects but also facilitates the development of students' ability to recognize, manage, and express emotions constructively, which ultimately makes a positive contribution to their academic achievement and social interactions.